Brand consistency and coherency at the London 2012 Olympic Games. (2nd January 2018) - Kenyon, James Andrew; Manoli, Argyro Elisavet; Bodet, Guillaume
Abstract: As brand management and brand perceptions attract more attention in both academia and in practice, examining the link or lack thereof between brand identity and image is becoming increasingly important. The existence of brand consistency and coherency is examined in this research, which aimed to evaluate whether the pre- or post-event brand image of the Olympic Games or the London 2012 Games, in the domestic UK population and media, were aligned with the brand identities of these objects. Online surveys and media content analysis revealed that both brands have yet to achieve consistency or coherency within these two key stakeholder groups, even though the brand image of the 2012 Games improved following the event. What this study suggests is that unless the brand owner takes key stakeholders' perceptions into consideration, a coherent and consistent brand identity does not necessarily equate to these being a feature of the brand image, with the connection between perceptions requiring additional attention.